Biological Effect of Audible Sound Control on Mung Bean (Vigna radiate) Sprout. (7th August 2014) - Cai, W.; He, H.; Zhu, S.; Wang, N.
Abstract : Audible sound (20–20000 Hz) widely exists in natural world. However, the interaction between audible sound and the growth of plants is usually neglected in biophysics research. Not much effort has been put forth in studying the relation of plant and audible sound. In this work, the effect of audible sound on germination and growth of mung bean ( Vigna radiate ) was studied under laboratory condition. Audible sound ranging 1000–1500 Hz, 1500–2000 Hz, and 2000–2500 Hz and intensities [80 dB (A), 90 dB (A), 100 dB (A)] were used to stimulate mung bean for 72 hours. The growth of mung bean was evaluated in terms of mean germination time, total length, and total fresh weight. Experimental results indicated that the sound wave can reduce the germination period of mung bean and the mung bean under treatments of sound with intensity around 90 dB and frequency around 2000 Hz and significant increase in growth. Audible sound treatment can promote the growth of mung bean differently for distinct frequency and intensity. The study provides us with a way to understand the effects and rules of sound field on plant growth and a new way to improve the production of mung bean.